The Use of Subconjunctival Erythropoietin Injection to Treat Avascular Bleb after Trabeculectomy: A Case Report - Yadgari, Maryam; Ansari , Iman; Hassanpour, Kiana (Journal of Ophthalmic and Optometric Sciences, 2019)
Purpose: To report a patient with avascular bleb after trabeculectomy who showed promising results after subconjunctival erythropoietin injection. Case Report: A 45-year-old woman with the diagnosis of primary open-angle glaucoma and history of trabeculectomy three years prior was admitted to our center. The corrected distance visual acuity (CDVA) was 20/20 in both eyes. Her ocular examination revealed an avascular and cystic bleb in the right eye. Seidel test was negative while bleb sweating was observed after fluorescein staining of the bleb area. Intraocular pressure (IOP) was 5 mmHg in the right eye. Erythropoietin (2000 unit in 0.1 ml) was injected subconjuctivally around the bleb area in the temporal quadrant. Six weeks after the injection, the bleb area just superior to the conjunctiva showed an increased fibrosis formation while the IOP remained the same as before injection.